The Effect of Oxytocin Massage on Breast Milk Production in Breastfeeding Mothers at the Galala Inpatient Health Center - Fitriyati Syahbudin; Reny Retnaningsih (Jurnal Siti Rufaidah, 2025)
Breast milk production in the early postpartum period often experiences obstacles due to physiological and psychological factors, which can affect the success of exclusive breastfeeding. Non-pharmacological interventions such as oxytocin massage are known to help stimulate the milk ejection reflex, but their application in primary health facilities is still limited. This study aims to determine the effect of oxytocin massage on breast milk production in breastfeeding mothers. The study design used a quasi-experimental approach with a one-group pretest–posttest design. The study sample consisted of 30 breastfeeding mothers who met the criteria and were selected using total sampling technique at the Galala Inpatient Health Center. Breast milk production was measured based on volume and clinical signs of breast milk production before and after the oxytocin massage intervention. Data analysis used the Wilcoxon Signed Rank Test. The results showed a significant increase in breast milk volume and signs of production after the intervention with a p-value < 0.001. This indicates that oxytocin massage is effective in increasing breast milk production through a neurohormonal stimulation mechanism that enhances the let-down reflex. In conclusion, oxytocin massage can be recommended as a lactation support intervention in primary care facilities to support successful exclusive breastfeeding.